RANGE OF PROBLEMS IN CUTTING SUBSTRATES BY A DIAMOND-TIPPED DISK IN p-i-n SILICON PHOTODIODES TECHNOLOGY - Kukurudziak, Mykola (Science-based technologies, 2022)
The article aims at solving problems of degradation of silicon p-i-n photodiodes parameters during cutting wafers into crystals by a disk with an outer cutting tip. A comparative analysis of methods of cutting silicon wafers into elements, the following methods are characterized, in particular: diamond scribing with subsequent breaking, laser cutting. While analyzing scientific publications, it was found out that laser control thermal spalling method becoming widely used, provides minimum defects along the cut. But, in turn, the method calls for solving a range of related problems that considerable complicate the treatment. Accordingly, it is advantageous to use this method of parting wafers into elements for cutting brittle materials, thin substrates or structures where stringent requirements for quality of the cut are placed. In cases, where it is difficult to use laser radiation or there are no strict requirements to roughness of edges of products, it is expedient to employ less labour-intensive and expensive methods of separation, cutting by a diamond disk with an outer cutting-tip, in particular. In this way, in commercial production of silicon quadrant p-i-n photodiodes with a guard ring, increase of dark currents values after cutting was observed. The growth of the dark current observed, needed to be investigated, to establish its causes and methods to avoid it. Accordingly, the purpose of this work is to study the mechanism of increase of photodiode dark currents and to establish optimal modes of cutting wafers by the method. In the course of the experiment, optimal undercut was determined to be 1/4 of the substrate thickness. The influence of the distance from the cut to the responsive elements on dark currents of the guard rings was investigated, and it was established that when the distance from the cut to the guard ring is 900 μm, degradation of dark current doesn’t take place (when bias voltage is 120V). When the distance from the cut to the active elements decreases, dark currents of the guard rings worsen. If a lower bias voltage is used, the distance from the cut to the guard ring may be decreased, and the dark current will be not deteriorated. The increase in dark currents of the responsive areas after the cutting process was not observed. The influence of the cutting disk velocity and the thickness of cutting blade on dark currents of photodiodes was also studied. The optimal velocity of the blade feed is 5 mm/s, and when the thickness of the diamond blade decreases, dark currents deteriorate reduces. Degradation of PD parameters after cutting occurs in consequence of acquired mechanical stresses and broken chemical bonds at the ends of crystals. This work determines optimal modes of cutting substrates into elements, allowing to avoid degradation of parameters of semiconductor devices.